Levels and Profiles of Functionality as Dimensions of University Quality: An Empirical Study of Universidad Complutense - De la Orden Hoz, Arturo; Asensio Muñoz, Inmaculada; Biencinto López, Chantal-María; González Barberá, Coral; Mafokozi Ndabishibije, José (Education Policy Analysis Archives, 2007)
This study comes out as a step forward in a research line focused on validating empirically a systemic model of university quality. The article defines university quality in terms of three dimensions: functionality, effectiveness and efficiency. The focus of the article is on the analysis of the dimension of functionality as a starting point in the process of identifying and validating indicators for the evaluation of university quality. The core of the article integrates the presentation of the level and profile of functionality of the university for the total sample and for three audiences: faculty, students and employers. For each audience the study emphasizes the evaluation of the extent to which the university accomplishes its functions as a whole institution (level) and for each separate function (profile), as well as the differences among different strata of each audience. Finally, the study points out the differences in the profiles of functionality of the university observed by the different audiences, both as a whole institution and for each function. In the conclusions, a global vision of the level of functionality of the university, evaluated by the three audiences, is established.